MODEL TASAWUF INTEGRATIF (STUDI FENOMENOLOGI MODEL PARADIGMA INTEGRASI TASAWUF DENGAN ILMU PENDIDIKAN ISLAM DI MADRASAH - Ruslan (Living Sufism: Journal of Sufism and Psychotherapy, 2022)
Islamic education has a more tangible spiritual transmission in the teaching process than general education. The clarity lies in the desire to develop all aspects of students in a balanced way. However, although Islamic religious education has been programmed since education at the elementary level to higher education, the contribution of PAI itself is still often questioned. Because the current portrait of Indonesian education is still far from what we all hoped for. This paper will examine about; 1) The urgency of PAI development, 2) getting to know the teachings of Sufism, 3) the paradigm and model of developing Islamic Education based on Sufism. The type of this research is library research using a descriptive-analytic approach. While the data source uses the principle of recency and the principle of relevance. Data analysis uses content analysis method to produce a clear and systematic literature review. The results of the study show that 1) the development of PAI is an absolute thing to do considering that Islamic religious education itself has a great goal, namely to produce people who are devoted to Allah SWT; 2) Sufism teachings are generally divided into 3 (three) schools of thought, namely akhlaqi Sufism, Irfani Sufism, and philosophical Sufism; 3) Sufism-based PAI development paradigm is more appropriate if it is carried out using an organism/systemic paradigm by integrating the existing values of Sufism in PAI learning in madrasas which in turn gives birth to a webbed pedagogy learning model.